Epidemiological profile of teenage pregnancy in northeastern Brazil: an ecological study (Research, Society and Development, 2022)
Objective: The present study aimed to describe the epidemiological profile of pregnant adolescents in northeastern Brazil in the period 2015 - 2019. Methodology: This is a descriptive, ecological study with a quantitative approach based on data obtained from information platforms such as the Brazilian Institute of Geography and Statistics (IBGE) and the Department of Informatics of the SUS (DATASUS) in the period from 2015 to 2019. Results: 811,662 teenage pregnancies were studied during the years 2015 to 2019 in the northeast of Brazil, where 94, 61% (767,930) of pregnant women were between 15-19 years old and 5.39% (43,732) were between 10-14 years old. Conclusion: It was concluded that the majority of pregnant adolescents in the Northeast are in the age group of 15 to 19 years old, most with 8 to 11 years of schooling, and among adolescents from 10 to 14 years old, with 4 -7 years of study, with a single marital status, who declared themselves to be brown. The prenatal follow-up consisted of 7 or more consultations, the delivery method was vaginal, with term births and newborns weighing between 3000g and 3999g.